2016
DOI: 10.1158/1538-7445.am2016-1778
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1778: A comparison study of the disparities of cervical cancer excess mortality between Black and Caucasian women in Alabama and the US

Abstract: Background: The main purpose of this study was to assess the disparity of cervical cancer (CerCancer) mortality rates change through time between Black and Caucasian women residing in Alabama and the US. Methods: The CerCancer behavioral risk factors and utilization of screening tests data were obtained from CDC's Behavioral Risk Factor Surveillance System (BRFSS) database. Baseline data and target objectives of utilization of CerCancer screening and mortality rates were obtained from Healthy Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…Significantly, in contrast, our recent study findings [40] regarding Cer-Cancer screening, showed high rates of CerCancer mortality, which was more than triple in Black Alabamians (between 2002 and 2012), despite their high screening rates (between 2000 and 2010), compared to their White counterparts. This study shows conclusively that in Alabama, a disparity still exists for the high CerCancer mortality in Blacks, despite the higher rates of screening as would otherwise be expected [40]. In spite of all this, Blacks were still more likely to be diagnosed with advanced stages of CerCancer, and their chances of surviving 5 years after diagnosis was lower compared to their White counterparts.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Significantly, in contrast, our recent study findings [40] regarding Cer-Cancer screening, showed high rates of CerCancer mortality, which was more than triple in Black Alabamians (between 2002 and 2012), despite their high screening rates (between 2000 and 2010), compared to their White counterparts. This study shows conclusively that in Alabama, a disparity still exists for the high CerCancer mortality in Blacks, despite the higher rates of screening as would otherwise be expected [40]. In spite of all this, Blacks were still more likely to be diagnosed with advanced stages of CerCancer, and their chances of surviving 5 years after diagnosis was lower compared to their White counterparts.…”
Section: Discussioncontrasting
confidence: 92%
“…In addition, according to the National Health Survey, similar CerCancer screening rates were reported among Black and White Americans [39]. Significantly, in contrast, our recent study findings [40] regarding Cer-Cancer screening, showed high rates of CerCancer mortality, which was more than triple in Black Alabamians (between 2002 and 2012), despite their high screening rates (between 2000 and 2010), compared to their White counterparts. This study shows conclusively that in Alabama, a disparity still exists for the high CerCancer mortality in Blacks, despite the higher rates of screening as would otherwise be expected [40].…”
Section: Discussionsupporting
confidence: 52%
“…A disproportionate number of cervical cancer deaths occur among racial/ethnic minorities, particularly Blacks than Whites. Although differences in prevalence rate and stage of disease at diagnosis may contribute to racial disparities in mortality, evidence of racial disparities in the receipt of treatment of other chronic diseases raises questions about the possible role of inequities in the receipt of cancer treatment ( Abdalla E, 2017 ). Our study indicated that surgical treatment for Black patients who were diagnosed with cervical cancer in rural BBC was significantly less common amongst Black than White patients.…”
Section: Discussionmentioning
confidence: 99%
“…This method allows for the use of data coming from ADPH, Cancer Registry and the enhanced surveillance aimed at treating Black patients living in these counties. The procedure provides the necessary input to the large-scale computational model for the analysis of different treatments as mitigations in the future ( Abdalla E, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation